2011
DOI: 10.1108/17511061111143025
|View full text |Cite
|
Sign up to set email alerts
|

Generation Y's perception of wine and consumption situations in a traditional wine‐producing region

Abstract: PurposeThis paper aims to offer an in‐depth analysis of Generation Y's choices concerning the consumption of wine and other alcoholic drinks by examining the consumption situations in a traditional wine‐producing country.Design/methodology/approachThe study applied the multinomial logit model involving a sample of Generation Y alcohol consumers in a city in Northern Italy. Choice sets were constructed using the Bayesian efficient design, and each choice set included four consumption situations: at bars or pubs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 39 publications
8
63
1
Order By: Relevance
“…This situation turned out to repeat itself in our population since we do not find significant differences between genders in wine consumption. On the other hand, other studies have shown that men drink slightly more wine than women and these differences worsen after 35 years [29][30][31][32][33][34][35][36][37][38][39][40][41]. We do not find such differences in our study as our population is between 18 and 30 years, and those differences in consumption are not yet observed.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…This situation turned out to repeat itself in our population since we do not find significant differences between genders in wine consumption. On the other hand, other studies have shown that men drink slightly more wine than women and these differences worsen after 35 years [29][30][31][32][33][34][35][36][37][38][39][40][41]. We do not find such differences in our study as our population is between 18 and 30 years, and those differences in consumption are not yet observed.…”
Section: Discussioncontrasting
confidence: 81%
“…In short, young consumers evaluate wine as a multifaceted category [31], so that, due to the complexity of this product, novice consumers often find it difficult to appreciate its quality, which can affect the decision and choice processes [32,33]. Young people, although they have limited experience, can assess wines using specific characteristics such as origin, harvest, label, brand and grape variety [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…287 correctly-completed questionnaires were analyzed. This sample is comparable in terms of size and characteristics to those used in numerous recent wine marketing researches (Agnoli et al, 2011;Concha et al, 2010;Espejel and Fardos, 2009;Latour and Latour, 2010;Orth et al, 2010;St James and Christodoulidou, 2011;Veale and Quester, 2009, etc.). In the first part of the questionnaire, focusing on the choice of the wine, the respondents had to recall the circumstances of their last purchase: specify its purpose choosing from six propositions and indicate the importance given to 30 attributes describing the wine.…”
Section: Methodsmentioning
confidence: 64%
“…Various studies have shown that considerable differences in wine consumption can be identified across generations what supports the market segmentation on the basis of age cohorts (e.g. Chrysochou et al, 2012;Agnoli et al, 2011;Barrena and Sanchez, 2009;Thach and Olsen, 2006;Thomas and Pickering, 2005). With respect to the benefits of wine consumption, it was found that young consumers perceive wine as a beverage, playing an important role in social occasions (Olsen et al, 2007).…”
Section: Cross-generational Wine Consumptionmentioning
confidence: 99%